Wordsworth's View of Nature Reflected in I Wandered Lonely as a Cloud - Du Xinyi (SHS Web of Conferences)
William Wordsworth, a great poet from the English Romantic era, is celebrated for his deep portrayals and evocative emotions of the natural world. The majority of his poems center around elements in nature, serving as the primary vehicle to convey his contemplation on the world. Thus, the crux of this research is examining Wordsworth’s viewpoint on nature, namely via a meticulous analysis of the poem I Wandered Lonely as a Cloud. The research demonstrates that Wordsworth depicts nature as a conscious and emotive being via the use of anthropomorphic methods, as shown in his portrayal of daffodils ‘dancing’ and ‘flashing’ in his poem. Anthropomorphic daffodils not only provide visual pleasure but are also a source of emotional and spiritual renewal. This understanding of nature not only helps readers understand the core idea underlying love poetry, but also has important consequences for considering the connection between humans and nature in modern civilisation. Wordsworth's poetry exemplify the enormous influence that nature has on human emotions, while underscoring its function as a comforting and inspiring source for the spirit.